Analysis of Mathematic Communication Ability to be Reviewed From Student Learning Creativity In Statistical Materials - Budi, Samuel; Darmawan, Handi; Saputro, Marhadi (Universitas Negeri Makassar, 2020)
This study aims to determine the extent of mathematical communication skills of students who have high learning creativity in statistics material in Class VIII of SMP Negeri 01 Putussibau, which are categorized in high, medium, and low learning creativity. The problem in this study is